Comparative Analysis of PID and Fuzzy Temperature Control System on Infant Warmer - Abdul Majid; Endang Dian Setioningsih; Abd Kholiq; Singgih Yudha Setiawan; Anilkumar Suthar (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
Infant Warmer is a life support equipment that is used to provide heat relief for normal and premature babies who are unable to maintain their own body temperature when in a new environment. The purpose of this research is to design an infant warmer using the DS18B20 sensor to analyze the efficiency and effectiveness between PID and fuzzy temperature control. This study used temperature settings of 34 °C, 35 °C, and 36 °C. The tool used for reference from standard measurements uses a standard infant warmer. When using the PID control used in the microcontroller detects the set temperature difference value with the actual temperature, the difference in value will be input to the PID control. The error value becomes PWM input on the PID control, the PID control will process the error value and determine the output value for the heater, the temperature sensor will read the actual temperature value which will be compared again with the temperature setting, the PID control will continue to process the error value and determine the PWM output value. until the actual temperature is equal to the setting temperature or the error value is zero